Planting arrangement and effects of planting density on tropical fruit crops—a review - Haque, Mohammad Amdadul; Sakimin, Siti Zaharah (MDPI, 2022)
With the growing importance of fruits as valuable food resources, attention has been paid in recent years to enhance productivity and quality. Increasing productivity per unit area through agronomic management is one of the important strategies to increase the production of fruit crops. Keeping this view, this review was undertaken to improve understanding of the planting arrangement and the effect of planting density on productivity and quality of fruit crops. This review will thus provide updated and in-depth information about the influence of planting density on yield and fruit quality, which will also be useful for the growers, consumers, exporters, and processing industry. In fruit crops, the effect of plant density and planting arrangement is well documented. From the review, it is understood that yield per unit area is the product of fruit yield plant−1 and the number of plants per unit area. Fruit size increases with a decreasing planting density, while total yield increases with an increasing density at a certain level. However, fruit quality decreases with an increasing planting density.